The protective effect of zinc, selenium, and chromium on myocardial fibrosis in the offspring of rats with gestational diabetes mellitus. Issue 3 (20th January 2023) - Deng, Haichao; Yao, Xueqiong; Cui, Ningning; Huang, Shanshan; Ge, Yanyan; Liu, Rui; Yang, Xuefeng
Abstract : Myocardial fibrosis in offspring with hyperglycemia is confirmed first; supplementation with zinc, selenium, and chromium to GDM mothers suppresses these changes in offspring. Abstract : The offspring of gestational diabetes mellitus (GDM) mothers are considered to be at the risk of cardiovascular diseases due to intrauterine hyperglycemia exposure. Our previous study showed that zinc, selenium, and chromium dramatically alleviated glucose intolerance in GDM rats and their offspring ( P < 0.05). However, the effects of these elements on the damage of the cardiac myocytes of GDM offspring and the underlying mechanisms have not been demonstrated. Here, we investigated the beneficial effects of zinc (10 mg per kg bw), selenium (20 μg per kg bw), and chromium (20 μg per kg bw) supplementation on myocardial fibrosis in the offspring of GDM rats induced by a high-fat and sucrose (HFS) diet. The results showed that maternal GDM induced glucose intolerance, oxidative stress, cardiac inflammation and myocardial fibrosis in offspring rats during different ages (3 days, 3 weeks, and adulthood), which were ameliorated by zinc, selenium and chromium supplementation ( P < 0.05). The activity of cardiac damage markers such as creatine kinase-myocardial band isoenzyme (CK-MB), lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) decreased by 40–60% in element-supplemented offspring compared to that in non-supplemented offspring of GDM dams ( P < 0.05). Moreover, maternal GDM-induced expression of fibrosis-related proteins and the transforming growth factor-beta 1 (TGF-β1)/small mothers against decapentaplegic homolog 3 (Smad3) signaling pathway in the heart tissue of offspring was down-regulated by zinc, selenium, and chromium supplementation ( P < 0.05). In conclusion, zinc, selenium, and chromium may play a protective role in maternal GDM-induced myocardial fibrosis in offspring from birth to adulthood by inactivating the TGF-β1/Smad3 pathway.